Tax Planning through Thin Capitalization in Multinational Corporations in Indonesia - Puspitorini, Gayatri Indah; Alfa Rahmiati, Alfa (Politeknik Ganesha Medan, 2024)
In an effort to achieve the goals of minimizing taxes and maximizing global profits, multinational companies use several strategies in their tax planning to obtain maximum global profits. Good tax planning will certainly be able to minimize the tax burden that must be paid without having to violate existing regulations, including using thin capitalization. This type of research is qualitative research, while the data collection technique in this research was carried out by following the research steps of library research. The aim of this research is to provide an overview of appropriate tax planning that can be carried out by Multinational Corporations (MNC) in Indonesia by using thin capitalization in accordance with existing laws and regulations in Indonesia. The results of this research are that MNCs in Indonesia in their tax planning should utilize a thin capitalization strategy by maximizing debt and capital in accordance with PMK-169/PMK.010/2015 rules, namely 4:1.